PENGARUH MEDIA SOSIAL, KUALITAS LAYANAN, DAN HARGA TERHADAP LOYALITAS PELANGGAN UNTUK BERKUNJUNG KE LAWANG SEWU - Scorina Dwiantari; Irene Nathalia Setiawan; Bambang Heriawan (JURNAL ILMIAH EDUNOMIKA, 2024)
TThe purpose of this research is to identify the relationship between customer loyalty to modern Semarang leisure spots and the following factors: price, service quality, and social media. Quantitative research methods are employed, with data collected through surveys. A stratified random sampling method that incorporates proportional random sampling was employed for the sampling process. Procedures for processing primary data using SPSS analysis tools, including multiple regression and sobel tests. The study found that customer loyalty is positively and significantly impacted by price, service quality, and social media. Specifically, it was found that social media had a positive and significant effect on customer loyalty with regard to visiting contemporary recreation places in Semarang City. Service quality and price also had positive and significant effects on customer loyalty in this regard. Keyword : Social Media, Quality of Service, Price, Customer Loyalty